Price Pressure Gaps An Application of P* Using Korean Data - Haas, Richard D. (International Monetary Fund, 1991)
This paper presents estimates of a price-pressure indicator for Korea. It does this by constructing measures of how much M2 velocity and output differ from their long-term values. This, in turn, involves estimating a demand for money function in an error correction framework in which interest rates in the unorganized money market help to account for the effects of ongoing financial liberalization. An equation explaining the Korean inflation rate is identified in which both the monetary variable--the velocity gap--and the real variable--the output gap--play important roles